Evaluation of learning transfer after a perinatal/neonatal palliative care virtual training course - Brady, Sinead; Parravicini, Elvira; Wool, Charlotte (Frontiers in Pediatrics, 2023)
Background: The success of a training can be determined by the degree of learning transfer. To address a gap in educational offerings during the pandemic, an interdisciplinary team developed and offered a three-day virtual course, called Next Level Perinatal Palliative Care Training. Objective: This study aimed to evaluate transfer of learning and practice from a virtual training course on perinatal/neonatal palliative care (PNPC) by a range of clinicians. Study Design: A descriptive prospective survey design was used to collect data at two time points, immediately following the training course and again six months later. Frequency and descriptive statistics were used to measure implementation of PNPC quality indicators, self-reported competence, and clinical facilitators and barriers. A t-test was used to compare participants’ anticipated learning transfer to actual learning transfer. Two open-ended items assessed benefits and drawbacks of virtual training. Results: At course completion participants anticipated opportunities to implement PNPC strategies with means of 84-87 and at the six-month mark the reported implementation had means ranging from 71-77. At six months post training, participants reported feeling competent/highly competent in each variable with frequency scores of 89- 98%. The opportunity to learn key concepts of PNPC and refresh skill sets ranked as the top facilitators, while top barriers were the lack of opportunity to use PNPC principles and the lack of funding. Conclusion: Learning transfer after a virtual training course of PNPC proved to be successful, with a high rate of self-reported actual implementation and competence at six months after the Training.